Lessons for Singapore from Schooling’s win - CHAN, David (Institutional Knowledge at Singapore Management University, 2016)
Joseph Schooling’s gold medal win at theRio Olympics over the weekend highlightsthe achievements of human potential andthe indomitable spirit of human nature